1999
DOI: 10.1111/1467-9507.00083
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and ‘Theory of Mind’: A Critique of the ‘Social Skills Deficit’ View of Anti‐Social Behaviour

Abstract: Bullying in schools has been found to be widespread. The popular stereotype of a bully, supported by theories based on the social skills deficit model, is of a powerful but 'oafish' person with little understanding of others. In this article, we trace the origin of this view, and present an alternative view: that some bullies, at least, will need good social cognition and theory of mind skills in order to manipulate and organise others, inflicting suffering in subtle and damaging ways while avoiding detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
332
6
44

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(408 citation statements)
references
References 48 publications
26
332
6
44
Order By: Relevance
“…In line with previous research (Toblin, Schwartz, Gorman, & Abou-ezzeddine, 2005), we found that t-bullying also related to children's expectations that they would gain positive results from behaving aggressively, which is associated with proactive aggression in youngsters (Smithmyer, et al, 2000) and reflects a deficit in the latter stages of the social information processing (Crick & Dodge, 1994). Our results support the suggestion of Sutton, Smith, & Swettenham (1999), that bullies do not have deficits in interpreting social cues, but in the latter stages of social information processing, during goal and response selection, where the expectancy of positive outcomes from a harmful act increases the likelihood of an aggressive response. In other words, the bullies in our study behave aggressively because of what they expect to gain.…”
Section: Bullying and Cyberbullying 23 23supporting
confidence: 92%
“…In line with previous research (Toblin, Schwartz, Gorman, & Abou-ezzeddine, 2005), we found that t-bullying also related to children's expectations that they would gain positive results from behaving aggressively, which is associated with proactive aggression in youngsters (Smithmyer, et al, 2000) and reflects a deficit in the latter stages of the social information processing (Crick & Dodge, 1994). Our results support the suggestion of Sutton, Smith, & Swettenham (1999), that bullies do not have deficits in interpreting social cues, but in the latter stages of social information processing, during goal and response selection, where the expectancy of positive outcomes from a harmful act increases the likelihood of an aggressive response. In other words, the bullies in our study behave aggressively because of what they expect to gain.…”
Section: Bullying and Cyberbullying 23 23supporting
confidence: 92%
“…These "bully victims" have been characterized as hyperactive, impulsive, and as experiencing more peer rejection, more academic difficulties, and more stressful and harsh home environments (see Schwartz, Proctor, & Chien, 2001), but represent only a small portion (1% to 12%) of students (Dulmus et al, 2006;Nansel et al, 2001;Solberg & Olweus, 2003;Spriggs, Iannotti, Nansel, & Haynie, 2007). Over the past four decades, research has also shown that many bullies are socially intelligent (Björkqvist, Österman, & Kaukiainen, 2000;Sutton, Smith, & Swettenham, 1999a, 1999b and enjoy considerable status in the peer group (Vaillancourt et al, 2003), leading to distinctions between socially marginalized and socially integrated bullies (Farmer et al, 2010). Adults may be less able to recognize bullying perpetrated by students who appear to be socially competent, wellfunctioning individuals.…”
Section: Different Types Of Bulliesmentioning
confidence: 99%
“…Such research however is based on peer to peer bullying; or educators bullying students. As age increases it is more difficult to carry out bullying, as victims become more capable of defending themselves (Sutton, Smith, & Swettenham, 1999).…”
Section: Differences In Years Of Teaching Etb and Burnoutmentioning
confidence: 99%